PENGARUH BRAND IMAGE, ELECTRONIC WORD OF MOUTH (E-WOM) DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK AIR MINUM GALON CRYSTALLINE PADA PT. PANCARAN KASIH ABADI - Arie Liyono (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
This study aims to determine the effect of: 1) brand image, 2) electronic word of mouth (e-WOM), and 3) price on purchasing decisions of Crystalline gallon drinking water products at PT. Pancaran Kasih Abadi. This research is a quantitative descriptive research by conducting a survey to reveal the influence of research variables. This research was conducted at PT. Pancaran Kasih Abadi Yogyakarta as the sole and official distributor of Crystalline gallon drinking water along with its agents, sub agents and retailers. Respondents in this study were 106 consumers of Crystalline drinking water. The data obtained were then processed by multiple regression analysis with the help of SPSS version 25. The results showed: 1) brand image has a positive and significant effect on purchasing decisions of Crystalline gallon drinking water, 2) e-WOM has a positive and significant effect on purchasing decisions of Crystalline gallon drinking water, 3) price has no significant effect on purchasing of Crystalline gallon drinking water, 4) brand image, e-WOM and price simultaneously have a positive and significant effect on purchasing decisions of Crystalline gallon drinking water.